Implementation of Web-Based Inventory System With Email Notifications for Stock Efficiency and Project Management at CV Bonanza - Naufal Meidhana Kenmahdy; Ahmad Jazuli; Esti Wijayanti (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
Material inventory management at CV Bonanza is still conducted manually, leading to report delays and data inaccuracies. This research aims to design a web-based inventory information system to address these problems. This study employs the Waterfall model for the system development life cycle (SDLC). The requirements analysis phase (as the requirements baseline) was conducted qualitatively from February to April 2025 through structured interviews with 4 stakeholders (owner, admin, foreman, and project executor) and workflow observation (analysis of 50 transactions). The system was implemented using PHP Native and MySQL, with an innovation focus on stock-project management integration, event-driven email notifications (PHPMailer), and a project-check transparency feature. System testing used the Black Box Testing method, covering 55 test scenarios (encompassing 100% of functional requirements). Initial testing found 2 defects (a 3.6% failure rate), which were subsequently fixed, resulting in 100% of scenarios being declared "Valid" upon re-testing. The main outcome of this research is a system prototype that is functionally valid. Claims of "efficiency" and "accuracy" are limited to design targets, as this study was restricted to functional testing and did not include non-functional testing (such as performance, usability/SUS, or security) or quantitative post-implementation impact evaluation.